Analysis of clogging factors in single-wing labyrinth drip irrigation tape. - Hui Zhang; Hongfei Tao; Yao Liu; Qiao Li; Youwei Jiang; Mahemujiang Aihemaiti; Wenxin Yang (PLoS ONE)
The clogging performance of single-winged labyrinth drip irrigation tapes is influenced by a variety of factors during the muddy fertilizer water irrigation process. In this paper, we designed a uniform orthogonal test to study the effects of fertilizer concentration, sediment content and working pressure on the clogging of single-wing labyrinth drip irrigation tapes. The observed data from the experiment were analysed and calculated using range analysis, variance analysis, and main-effect multiple comparison analysis, then the optimal working conditions were determined. The results of the study showed that fertilizer concentration and sediment content had a significant effect on the average relative flow, and the degree of influence of each influencing factor on the average relative flow was as follows: sediment content > fertilizer concentration > working pressure. The average relative flow of water-fertilizer-integrated irrigation under muddy-water conditions decreased with the increasing of irrigation frequency, and accelerate the clogging of dripper. Eventually we concluded that muddy fertilizer water irrigation exacerbated the clogging of dripper. The highest average relative flows across three sediment levels occurred under the F1 treatment, measuring 0.699, 0.681, and 0.668 for type-H1, type-H2, and type-H3 tapes, respectively. The research results can provide a reference basis for the optimal design of structural parameters of single-wing labyrinth drip irrigation tape channel.